Creativity of Muhammadiyahan Teachers in Motivating Students to Join the Muhammadiyah Student Association Organization - Elsa; Mukhlishah; Ibrohim, Iim; Supala; Fadlani Salam, Mochamad (Yayasan Mentari Madani, 2023)
SMP Muhammadiyah 10 Bandung was established in 1974. Since its establishment until now, from year to year it has always increased, especially in terms of Acceptance of New Students. This shows that the work of SMP Muhammadiyah 10 Bandung in helping the government to educate the nation can be felt by the community. This study aims to determine the extent of the success of the creativity of teachers of Muhammadiyahan subjects in motivating inner grade students by identifying: 1) student motivation to follow the HDI organization, 2) creativity of Muhammadiyahan teachers, 3). supporting and inhibiting factors of creativity of Muhammadiyahan teachers in motivating students to join the HDI organization. 4). The results of Muhammadiyahan Teacher Creativity in Motivating Grade 8 Students of SMP Muhamadiyah 10 Bandung City Participating in the Student Association Organization in Motivating Grade 8 Students of SMP Muhamadiyah 10 Bandung City Participating in the Muhammadiyah Student Association Organization. The method used in this study is descriptive analysis with a qualitative approach. Data collection through observation, interviews, and documentation. The results of this study show the creativity of teachers by presenting material using the Mind Mapping method and conveying it to students very well so that it is easy to understand and students also have the motivation to join the HDI organization because of their own desires; want to assume responsibilities such as wanting to be on the committee; exercise courage; practice communicating well